A new approach for balancing the microbial synthesis of ethyl acetate and other volatile metabolites during aerobic bioreactor cultivations - Christian Löser (Engineering in Life Sciences, 2021)
Abstract Ethyl acetate is an organic solvent with many industrial applications, currently produced by energy‐intensive chemical processes based on fossil carbon resources. Ethyl acetate can be synthesized from renewable sugars by yeasts like Kluyveromyces marxianus in aerobic processes. However, ethyl acetate is highly volatile and thus stripped from aerated cultivation systems which complicate the quantification of the produced ester. Synthesis of volatile metabolites is commonly monitored by repeated analysis of metabolite concentrations in both the gas and liquid phase. In this study, a model‐based method for quantifying the synthesis and degradation of volatile metabolites was developed. This quantification of volatiles is solely based on repeatedly measured gas‐phase concentrations and allows calculation of reaction rates and yields in high temporal resolution. Parameters required for these calculations were determined in abiotic stripping tests. The developed method was validated for ethyl acetate, ethanol and acetaldehyde which were synthesized by K. marxianus DSM 5422 during an iron‐limited batch cultivation; it was shown that the presented method is more precise and less time‐consuming than the conventional method. The biomass‐specific synthesis rate and the yield of ethyl acetate varied over time and exhibited distinct momentary maxima of 0.50 g g‒1h‒1 and 0.38 g g‒1 at moderate iron limitation.